2019
DOI: 10.1002/mrc.4825
|View full text |Cite
|
Sign up to set email alerts
|

Practical aspects of oligopeptide AAKLVFF as an alignment medium for the measurements of residual dipolar coupling of organic molecules

Abstract: Practical aspects of the oligopeptide AAKLVFF as an alignment medium are discussed, including large‐scale synthesis of the oligopeptide, detailed description of preparation of the alignment medium, and acquisition of the RDCs. The resulting orienting medium is stable and highly homogeneous with tunable alignment strength in methanol. We demonstrated its applicability on the stereochemical elucidation of two natural products, oridonin and α‐santonin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The measurement of 13 C NMR chemical shifts is done for each data set, and the RCSA values are obtained as described by Liu and co-workers. , A description of several alternative methods for RCSA measurement, with references, can be found in the Supporting Information. Recently, a method employing self-assembling polypeptides was reported that allowed for the measurement of the 13 C NMR spectrum in an isotropic state, and then after an equilibration time ranging from hours to weeks, a complementary 13 C spectrum could be acquired in an aligned condition . Work in the Gil lab demonstrated that RDCs can be measured in a single experiment when using compressed gels due to the fact that after a certain degree of compression, the gels buckle and generate pockets of isotropic solvent, which are never eliminated. , The amount of buckling depends on the degree of polymeric cross-linking and the length of the gel …”
mentioning
confidence: 99%
“…The measurement of 13 C NMR chemical shifts is done for each data set, and the RCSA values are obtained as described by Liu and co-workers. , A description of several alternative methods for RCSA measurement, with references, can be found in the Supporting Information. Recently, a method employing self-assembling polypeptides was reported that allowed for the measurement of the 13 C NMR spectrum in an isotropic state, and then after an equilibration time ranging from hours to weeks, a complementary 13 C spectrum could be acquired in an aligned condition . Work in the Gil lab demonstrated that RDCs can be measured in a single experiment when using compressed gels due to the fact that after a certain degree of compression, the gels buckle and generate pockets of isotropic solvent, which are never eliminated. , The amount of buckling depends on the degree of polymeric cross-linking and the length of the gel …”
mentioning
confidence: 99%
“…To double confirm the assigned structure, therefore, we measured the 1 D CH RDCs of 1 in alignment media following our established protocol and fitted them with theoretic RDCs of DFT optimized geometries of 1a and 1b (Figure ). As a result, 1a matched the experimental data well, showing a decent Q value (0.087), which was better than that of 1b (0.186). Thus, the planar structure and relative configuration of xylarichalasin A were determined to be 1a .…”
mentioning
confidence: 74%
“…To further confirm this assumption, residual dipolar coupling (RDC), a spatial-sensitive parameter, was employed to provide more evidence. The 1 D CH measurement was performed in the AAKLVFF oligopeptide alignment media under the guidance of the established protocol . The theoretical RDCs were calculated by the singular value decomposition (SVD) method in Mspin 2.3.4 software, and the Q factor was used as the estimate of average disagreement in percentage between experimental and calculated RDCs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The RDC data of chaetolactam A ( 1 ) was collected as the difference D = T – J between the couplings measured in the anisotropic and isotropic samples using the CLIP-HSQC experiment (Table S7). The anisotropic sample was prepared with the AAKLVFF oligopeptide at the final concentration about 30 mg/mL and tested the align strength in quadrupolar splitting of 18.6 Hz in the MeOD deuterium signal.…”
Section: Experimental Sectionmentioning
confidence: 99%